2014
DOI: 10.1002/acn3.96
|View full text |Cite
|
Sign up to set email alerts
|

A novel dysferlin mutant pseudoexon bypassed with antisense oligonucleotides

Abstract: ObjectiveMutations in dysferlin (DYSF), a Ca2+-sensitive ferlin family protein important for membrane repair, vesicle trafficking, and T-tubule function, cause Miyoshi myopathy, limb-girdle muscular dystrophy type 2B, and distal myopathy. More than 330 pathogenic DYSF mutations have been identified within exons or near exon–intron junctions. In ~17% of patients who lack normal DYSF, only a single disease-causing mutation has been identified. We studied one family with one known mutant allele to identify both t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 53 publications
(67 reference statements)
3
27
0
Order By: Relevance
“…A similar pathogenic effect has been proven to occur from the first deep intronic mutation (c.4886+1249G>T, intron 44) described in this gene . This latter mutation was found to recur in compound heterozygosity in patients with only 1 mutation detected (in 2 of 8 cases in 1 study and in 1 of 33 cases in another). Large genomic rearrangements have been reported to be pathogenic, the most frequent of which is the c.2512‐?_3174+?del, and others are quoted in public mutation databases.…”
Section: Genetic Diagnosissupporting
confidence: 56%
See 1 more Smart Citation
“…A similar pathogenic effect has been proven to occur from the first deep intronic mutation (c.4886+1249G>T, intron 44) described in this gene . This latter mutation was found to recur in compound heterozygosity in patients with only 1 mutation detected (in 2 of 8 cases in 1 study and in 1 of 33 cases in another). Large genomic rearrangements have been reported to be pathogenic, the most frequent of which is the c.2512‐?_3174+?del, and others are quoted in public mutation databases.…”
Section: Genetic Diagnosissupporting
confidence: 56%
“…Several studies have used mRNA analysis to demonstrate that many intronic mutations actually disrupt correct mRNA splicing . A similar pathogenic effect has been proven to occur from the first deep intronic mutation (c.4886+1249G>T, intron 44) described in this gene . This latter mutation was found to recur in compound heterozygosity in patients with only 1 mutation detected (in 2 of 8 cases in 1 study and in 1 of 33 cases in another).…”
Section: Genetic Diagnosismentioning
confidence: 91%
“…This splicing causes an in‐frame insertion of 59 additional amino acids in the dysferlin protein 39. This intronic variant segregated in a compound heterozygous state with the other pathogenic variant in two siblings (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Another group has also demonstrated that a mutant dysferlin pseudoexon could be skipped [34]. Such an approach has already been successfully applied in the case of DMD.…”
Section: Discussionmentioning
confidence: 99%
“…Exon skipping could also be used to remove pseudoexons. Recently, a mutation creating a pseudoexon between exons 44 and 45 of DYSF has been identified [34, 46]. Exon skipping using an AON targeting this pseudoexon restored a normal mRNA and increased dysferlin expression, opening the way for such an approach in dysferlinopathies [34].…”
Section: Discussionmentioning
confidence: 99%